Effects of Poria cocos extract on metabolic dysfunction-associated fatty liver disease via the FXR/PPARα-SREBPs pathway - Jinbiao He; Yu Yang; Fan Zhang; Yanjuan Li; Xiaosi Li; Xuemei Pu; Xudong He; Mei Zhang; Xinxing Yang; Qiuman Yu; Yan Qi; Xuefang Li; et al. (Frontiers Media S.A., 2022)
Despite the increase in the global prevalence of metabolic dysfunction-associated fatty liver disease (MAFLD), no approved drug currently exists for the disease. Poria cocos (Schw.) Wolf (P. cocos) is a medicinal mushroom belonging to a family of polyporaceae widely used in TCM clinics to protect the liver and treat obesity. However, its efficacy, practical components, and underlying mechanism against MAFLD are yet to be determined. In this study, we evaluated the effects of Poria cocos (P. cocos) ethanol extract (EPC) on hepatic dyslipidemia, steatosis, and inflammation by both bioinformatics analysis and MAFLD rats induced by HFD feeding. We found EPC treatment dramatically reduced lipid accumulation, inflammatory cell infiltration, and liver injury. EPC reduced serum TC, TG levels, and hepatic TG, TBA, and NEFA contents. UHPLC Q-Trap/MS examination of BA profiles in serum and feces showed that EPC increased fecal conjugated BAs, decreased free BAs, and improved BA metabolism in HFD-fed rats. Western blot and RT-qPCR analysis showed that EPC could activate hepatic FXR and PPARα expression and reduce CYP7A1 and SREBP-1c expression. Systemic pharmacology combined with molecular docking suggested that poricoic acid B and polyporenic acid C, the major active compounds in EPC, could ameliorate lipid homeostasis by activating the nuclear receptor PPARα. We further confirmed their inhibition effects of lipid droplet deposition in steatized L-02 hepatocytes. In summary, EPC alleviated HFD-induced MAFLD by regulating lipid homeostasis and BA metabolism via the FXR/PPARα-SREBPs signaling pathway. P. cocos triterpenes, such as poricoic acid B and polyporenic acid C, were the characteristic substances of P. cocos for the treatment of MAFLD.